If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -2a + 20 = 48 Reorder the terms: 13 + 20 + -2a = 48 Combine like terms: 13 + 20 = 33 33 + -2a = 48 Solving 33 + -2a = 48 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-33' to each side of the equation. 33 + -33 + -2a = 48 + -33 Combine like terms: 33 + -33 = 0 0 + -2a = 48 + -33 -2a = 48 + -33 Combine like terms: 48 + -33 = 15 -2a = 15 Divide each side by '-2'. a = -7.5 Simplifying a = -7.5
| 1523+p=2766 | | 146/20 | | 2x-90=3/4x | | (3n-8)=5+8 | | 12X^6-4X^4/2X^3 | | -5(1-8n)+6(-4-7n)=-35 | | X+14+x-38=180 | | 2y(3-x)+7(x-2y)= | | 4e+21= | | F(4)=(1/5) | | x^2+9x^2+220=0 | | 5x2/1 | | -6(2+4x)-8=7(-4x-4) | | y/5=2=-8 | | -1x=20 | | 3a-6=2(a+1)+9a+1 | | 2b-4=21 | | 3(2x-6)=2(3t-9) | | x/6=x/3-1 | | F(4)=3(4)-12 | | 4-3n+6=10 | | 7x-3=-x+8 | | -(-5/2x-3/2)=-3/2+x | | -1/2-(5x-9)=17 | | 6v-2v=36 | | x/2−7=14 | | 10w-15w^3=0 | | .6(3x+9)=-2(2x+6) | | (x+1)-(1-x)=(x-1)-(2-2x) | | 2A-k=w | | 3-3x=-2x+7 | | -11/3+3/2b=5/2(b-5/3) |